1985
DOI: 10.1139/f85-014
|View full text |Cite
|
Sign up to set email alerts
|

Natural Hybridization between Steelhead Trout (Salmo gairdneri) and Coastal Cutthroat Trout (Salmo clarki clarki) in Two Puget Sound Streams

Abstract: A genetic investigation of anadromous trout populations in the Puget Sound area revealed numerous juvenile individuals from two streams with electrophoretic phenotypes consistent with those expected for hybrid descendents of steelhead trout (Salmo gairdneri) and coastal cutthroat trout (S. clarki clarki). The likelihood of hybridization was evaluated with a hybrid index measuring the relative probability that the combined genotype for a particular fish at several diagnostic loci could have arisen by random mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
108
2
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 23 publications
2
108
2
1
Order By: Relevance
“…Considering that all tested males exhibited high fertilization rates in the control crosses, the obtained results suggest the dominance of some males over others during the pooled-milt fertilization. Spermatozoa competition in the fertilization of an egg pool with pooled milt of Atlantic salmon was observed by Campton & Utter (1985). Witlher (1988) found dominance of some males of Oncorhynchus tshawytscha in crosses with pooled milt, with variations of 1.4 to 75.6%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that all tested males exhibited high fertilization rates in the control crosses, the obtained results suggest the dominance of some males over others during the pooled-milt fertilization. Spermatozoa competition in the fertilization of an egg pool with pooled milt of Atlantic salmon was observed by Campton & Utter (1985). Witlher (1988) found dominance of some males of Oncorhynchus tshawytscha in crosses with pooled milt, with variations of 1.4 to 75.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Paternal effects on early life history are often obscured and unexplained when sperm from multiple males are mixed during fertilization (Rideout et al, 2004). Previous research has demonstrated that spermatozoa competition in pooled-milt results in different paternity contributions from potential male parents, which reduces the effective size of the broodstock (Campton & Utter, 1985;Allendorf & Ryman, 1987). Reported variations in the fertilizing capacity of pooled-milt were confirmed by the verification of family relationships for Chinook salmon Oncorhynchus tshawytscha (Walbaum) (Gharret & Shirley, 1985;Withler, 1988;Withler & Beacham, 1994), rainbow trout Oncorhynchus mykiss (Walbaum) (Gile & Ferguson, 1995;Herbinger, 1995), Atlantic halibut Hippoglossus hippoglossus (L.) (Ottesen et al, 2009) and common carp Cyprinus carpio (L.) (Kaspar et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We used a simple hybrid index (Campton and Utter 1985;Rubidge and Taylor 2004) to classify individuals as pure bull trout, pure brook trout or bull trout 9 brook trout hybrids. For each individual the number of brook trout alleles present was summed and divided by the total number of alleles.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Natural interbreeding between steelhead and cutthroat has been reported in the state (Campton and Utter 1985), so there is also the posslbiiity of Type 3 risk. Habitat preferences probably iimlt the opportunity for Interactions between the two species, so the risks are probably negligible.…”
Section: Yakima Cutthroat Trout (Nontarget)mentioning
confidence: 99%